Planning Befriends Women: A Look of a Gender Responsive City in the Colombian Context - Yancili Lozano-Torres (Revista Iberoamericana de Estudios de Desarrollo)
Gender is considered the most universal form of inequality. Therefore, a just and sustainable development cannot, and should not, be conceived without gender equality (GE), as recognized by the 2030 Agenda for Sustainable Development. Several Latin American countries are making subs- tantial progress in terms of critical aspects of GE. For Colombia, the path towards gender equality starts from nationwide mandatory laws to be implemented at the local level. In this study, it is used data collected for a Convergent Parallel Mixed Method to conduct a comprehensive assessment of efforts towards GE in Colombian municipalities. Data collected are employed from the municipal de- velopment plans (PDMs), cities’ websites, and archival material. In this paper, I mainly present the results of the qualitative phase that uses a Qualitative Content Analysis (QCA). Results indicate that efforts towards GE in Colombian municipalities are portrayed through programs and initiatives to address the internationally recognized women’s agenda.